Therapeutic outcomes of intralesional dexamethasone and hyaluronidase in OSMF: A clinical pre-post intervention study. - Shankar, Daya; Kumar, Sanjeev; Dwivedi, Hari Krishn (Student's Journal of Health Research Africa, 2025)
Background The increasing fibrosis of the submucosal tissues is the hallmark of oral submucous fibrosis (OSMF), which is considered a progressive and chronic disorder of the oral mucosa that causes discomfort, tissue stiffness, and limited mouth opening. Objectives- This study was carried out to assess the impact of intra-lesional corticosteroids in the treatment of patients with OSMF, taking into consideration the previous research as well as the therapeutic benefits of corticosteroids. Materials and methods The study was an observational, multicentric study in nature. The study was done for nine months. In all, 105 patients were enrolled. Participants had to be willing to provide their consent, be between the ages of 18 and 50, and have a positive history of habits to be eligible. Results Among the 105 participants, the majority were male (67.6%) and aged between 28–37 years (48.6%). Most had only completed primary education (45.7%) and were engaged in unskilled occupations (56.2%), with nearly half residing in rural areas (49.5%). With a p-value of less than 0.001, the mean mouth openness rose from 26.12 ± 3.10 mm to 30.17 ± 4.20 mm. In a similar vein, the mean Visual Analogue Scale (VAS) score dropped significantly after treatment, from 7.01 ± 1.50 to 2.98 ± 1.98 with a p-value < 0.001. Conclusion Before and following treatment, the burning sensation VAS scores significantly decreased, indicating a considerable improvement in opening of the mouth, according to the current study's findings. Recommendation Regular intralesional administration of dexamethasone and hyaluronidase is recommended as an effective, minimally invasive treatment for improving mouth opening and reducing symptoms in patients with oral submucous fibrosis.